Conservation Status and Habitat Preferences of Common Warthog (Phacochoerus Africanus) in Old Oyo National Park, Nigeria - A.J. Adeola; A.I. Adeyemo; B.N. Ejidike; O.E. Olaniyi; O.A. Akande; S.R. Ajayi; O.K. Azeez (Journal of Applied Sciences and Environmental Management, 2021)
This study assessed the conservation status and habitat preference of Common warthog in Old Oyo National Park, Nigeria using direct sighting and line transect method. The abundance estimate and encounter rate of common Warthog in the study area from 2018-2019 showed that year 2018 recorded 213 individuals at an encounter rate of 0.38/km while year 2019 recorded 184 individuals at an encounter rate of 0.32/km while the mean abundance estimate of common Warthog are 4.65±0.64 and 1.71±0.48 which represents 156 and 58 individuals at encounter rate of 0.55/km and 0.20/km in the wet season and dry season of year 2018 compared to year 2019 with average abundance estimate value of 4.00±0.85 and 1.41±0.61 which represents 135 and 48 individuals at an encounter rate of 0.47/km and 0.17/km for wet and dry season respectively. The mean age structure and sex ratio of the observed warthog population during dry and wet seasons revealed that juveniles had highest mean of age structures among the populations observed across the seasons. The habitat preference of common warthog revealed that they are mostly found in mixed woodland and open savanna with 112 observation and the lowest was recorded in the outcrop vegetation and open savanna with 21 individuals.in the wet season. During the dry season, mixed woodland/open savanna and Riparian grassland had the highest sightings of 45 and 33 individuals each. The outcrop vegetation/open savanna had the lowest observation of 1 individuals only. The study also recommends that more aspect of the ecology of the animal should be studied in details and emphasis should be placed on the habitat requirements.